(untitled) (Research, Society and Development, 2022)
Gastritis is defined as a progressive pathology associated with an inflammatory process of the mucosal region of the stomach. This can eventually cause cellular changes from a non-atrophic state to an atrophic state until it reaches an intestinal metaplasia and, finally, gastric neoplasia. Its incidence and prevalence have increased over everyday life, with an increase in bad eating habits, stress and chronic consumption of alcohol and other drugs. In this perspective, knowing that the use of natural products of medicinal plants in the treatment of pathologies is very broad and effective in combating infections, the present study aimed, through a literature review, to understand and discuss the herbal medicine used in the treatment of gastritis. In nature, there is a wide variety of natural antioxidants that are different in their composition, physical and chemical properties, mechanism and place of action. Thus, despite the existence of intensive studies on the chemical contents in numerous plants used worldwide in folk medicine for the treatment of gastritis and ulcers, the complete composition data are still insufficient to predict all current activities and mechanisms of action. Thus, the use of medicinal plants as plant protection or in combination with antibiotics for the treatment of gastritis is an active field of research.